1984
DOI: 10.1002/lsm.1900040105
|View full text |Cite
|
Sign up to set email alerts
|

Application of hematoporphyrin derivative and laser‐induced photodynamical reaction in the treatment of lung cancer: A preliminary report on 21 cases

Abstract: This paper reports results of hematoporphyrin derivative based on photodynamic therapy (PDT) of 24 lung cancer lesions in 21 patients that were followed at least three months. Three of 24 lesions exhibited complete remission and 20 of 24 lesions exhibited a response to PDT. Tumors in twenty of twenty-one patients exhibited visually discernible hematoporphyrin derivative fluorescence upon irradiation with the 514-nm line from an argon ion laser. There were no severe complications due to PDT. The hematoporphyrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Complete response was observed in 70% of lesions, and 48% of patients required subsequent surgery for incomplete response, recurrence, or second primary (44). A number of other studies have demonstrated similar pathological response and safety profile for PDT in early-stage lesions larger than 1 cm (45)(46)(47)(48).…”
Section: Focused Reviewsmentioning
confidence: 82%
“…Complete response was observed in 70% of lesions, and 48% of patients required subsequent surgery for incomplete response, recurrence, or second primary (44). A number of other studies have demonstrated similar pathological response and safety profile for PDT in early-stage lesions larger than 1 cm (45)(46)(47)(48).…”
Section: Focused Reviewsmentioning
confidence: 82%
“…University of Southern California Medical School investigators reported a 97% complete response rate in 35 patients with predominantly primary NSCLC (n = 29) within the tracheobronchial tree, 41 and independent reports from Chinese investigators revealed 96% and 97% response rates in 21 patients with 24 bronchogenic carcinomas 42 and 54 patients with 69 bronchogenic carcinomas, 43 respectively.…”
Section: Non-small Cell Lung Cancermentioning
confidence: 98%
“…Several PDT phase II and phase III studies have been published [26][27][28][29][30][31][32][33]. In general, they all showed that recanalization of the tracheobronchial tree can be achieved, irrespective of the previous treatments given to the patients.…”
Section: Clinical Resultsmentioning
confidence: 99%